Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/asia.200800448
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of the Deoxysugar Part of Versipelostatin by Direct and Stereoselective Glycosylation and Revision of the Structure of the Trisaccharide Unit

Abstract: Efficient synthesis of the deoxysugar part of versipelostatin (VST) was achieved by direct and stereoselective glycosylation of the reduced VST aglycon. Activation of 2-deoxyglycosyl imidate with IBr under basic conditions enables alpha-selective glycosylation of beta-2-deoxylglycosides without anomerization. Comparison of the synthetic and natural VST products using NMR indicates that versipelostatin has a beta-D-digitoxose-(1,4)-alpha-L-oleandrose-(1,4)-beta-D-digitoxose trisaccharide. In addition, results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…71b In addition to these studies, Takahashi et al demonstrated the importance of the l -oleandrose sugar for the bioactivity, and changes in the oxidation state of C-7 had no effect on biological activity. 72 …”
Section: Biology Of Spirotetronate Polyketidesmentioning
confidence: 99%
“…71b In addition to these studies, Takahashi et al demonstrated the importance of the l -oleandrose sugar for the bioactivity, and changes in the oxidation state of C-7 had no effect on biological activity. 72 …”
Section: Biology Of Spirotetronate Polyketidesmentioning
confidence: 99%
“…[18][19][20] As shown in Scheme 38.9, treatment of the 4-O-benzylsulfonylolivosyl imidate 21 and 23 with I 2 and a catalytic amount of triethylsilane in toluene at À94 C provided the 2-deoxy-b-glycoside 24 in 94% yield with a nearly complete b selectivity (a/b ¼ 5/>95). [18][19][20] As shown in Scheme 38.9, treatment of the 4-O-benzylsulfonylolivosyl imidate 21 and 23 with I 2 and a catalytic amount of triethylsilane in toluene at À94 C provided the 2-deoxy-b-glycoside 24 in 94% yield with a nearly complete b selectivity (a/b ¼ 5/>95).…”
Section: Direct Synthetic Methodsmentioning
confidence: 99%
“…Obviously, the required modification step after construction of the sugar chain would increase the number of synthetic steps, and these would not be adaptable to the synthesis of 2‐ O ‐methyl‐α‐fucosides possessing an equatorial‐orientated C2 oxygen functional group. On the other hand, we had previously reported an efficient synthesis of 2‐deoxy‐α‐glycosides via the glycosidation of 2‐deoxyglycosyl imidates with IBr and n Bu 4 NBr under basic conditions . We further speculated that this method could involve a S N 2‐like substitution of in situ‐generated and unstable β‐glycosyl halides with glycosyl acceptors that could provide the 2‐deoxy‐α‐glycosides, which would make it adaptable to the direct synthesis of 2‐ O ‐methyl‐α‐glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we had previously reported an efficient synthesis of 2-deoxy-a-glycosides via the glycosidation of 2-deoxyglycosyl imidates with IBr and nBu 4 NBr under basic conditions. [12] We further speculated that this method could involve aS N 2-like substitution of in situ-generated and unstable b-glycosyl halides with glycosyla cceptors that could provide the 2-deoxy-a-glycosides,w hich would make it adaptable to the direct synthesis of 2-O-methyl-a-glycosides. Herein, we report the preparation of PGL-1 and PGL-tb1 containing 4-bromophenyl glycosides by direct a-selective glycosidation of 2-O-methyl-glycosyl imidates and modification of the glycosides by sequential Suzuki-Miyaura palladium-catalyzedc ross-cou-pling using ab oracyclane.…”
Section: Introductionmentioning
confidence: 99%